1994
DOI: 10.1002/jmv.1890430319
|View full text |Cite
|
Sign up to set email alerts
|

A thymidine kinase deficient HSV‐2 strain causes acute keratitis and establishes trigeminal ganglionic latency, but poorly reactivates in vivo

Abstract: The incidence of herpetic keratitis following intranasal or direct ocular infection with thymidine kinase-negative (TK-) strains of herpes simplex virus (HSV)-2 has not been well studied, and the role of the TK gene in the establishment of latency and virus reactivation is controversial. To determine whether a TK- strain of HSV-2 could establish trigeminal ganglionic latency and be reactivated in vivo to produce recurrent keratitis or nervous system infection, an animal model of acute and recurrent infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…However, TKmutant virus is pathogenic in humans, causing acute keratitis and establishing latency in trigeminal ganglion, and hence cannot be used clinically. 43 Interestingly, HSV-2 DNA has recently been shown to directly stimulate TLR9, suggesting that both TK -HSV-2 and IVAG CpG-ODN alone may mediate the up-regulation of vaginal DC through a common TLR9-mediated pathway. To this end, CpG-ODN delivery may well be a viable means of expanding mucosal tissue APC in immuno-compromised individuals in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, TKmutant virus is pathogenic in humans, causing acute keratitis and establishing latency in trigeminal ganglion, and hence cannot be used clinically. 43 Interestingly, HSV-2 DNA has recently been shown to directly stimulate TLR9, suggesting that both TK -HSV-2 and IVAG CpG-ODN alone may mediate the up-regulation of vaginal DC through a common TLR9-mediated pathway. To this end, CpG-ODN delivery may well be a viable means of expanding mucosal tissue APC in immuno-compromised individuals in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…After euthanasia, using 100 mg/kg sodium nembutal and transcardial perfusion with PBS, brains were removed and fixed in formalin or 1 mM sodium m-periodate, 75 mM lysine, 2% paraformaldehyde in 37 mM phosphate buffer, pH 7.4 for 24 h [46,48,49,50]. The brains were then cut into 11-12 blocks, processed for paraffin embedding, and sectioned [48].…”
Section: Histological Analysesmentioning
confidence: 99%
“…Many studies; have shown that TK~ deletion mutants establish latent infections in mouse trigemina! ganglia which fail to reactivate or reactivate poorly when ganglia are cocultivated with susceptible indicaior cells [87][88][89]. TK"" mutants cause much concern because of their maintained pathogenecity in animal studies since the TK phenotype does not necessarily attenuate the ability to induee disease in different animal models [81,89].…”
Section: / Pathogenicity Of Drug-resistant Variants Of Herpes Simpmentioning
confidence: 99%
“…ganglia which fail to reactivate or reactivate poorly when ganglia are cocultivated with susceptible indicaior cells [87][88][89]. TK"" mutants cause much concern because of their maintained pathogenecity in animal studies since the TK phenotype does not necessarily attenuate the ability to induee disease in different animal models [81,89]. Concerning the neurovirulence, PFU/LD^,, ratios resulting from intracerebra] inocu]ation indicate that differences in the pathogcnicities of viruses with different TK phenotypes are greater in this model than in the skin infeetion model.…”
Section: / Pathogenicity Of Drug-resistant Variants Of Herpes Simpmentioning
confidence: 99%